New landscapes of the post-industrial city - Zimpel, Jadwiga (Polskie Studia Krajobrazowe, 2019)
This paper attempts to analyze modern urban space in the context of intercepting the effects of biopolitical production by means of a conceptual apparatus taken from urban landscape studies. Among the discussed sections of urban space, which illustrate the issue undertaken in this text, there are first and foremost places that focalize and intertwine practices of urban design, landscape architecture, design and media initiated by local governments, institutions, and private investors. All of these practices strive to create a new type of urban landscapes, characterized by their simultaneous functioning as sights and as “urban stages.” Following from the above findings, this paper aims to describe the listed forms of land use in terms derived from cultural concepts of landscape, considering the latter to be a useful tool for explaining the relations between modern urban subjects and the environment they exist in.